DESIGN AND DEVELOPMENT OF MULTIMEDIA ANIMATION OF ROD MATERIALS DEFLECTION IN THE TOPICOF MATERIALS STRENGTH - Saputra, Nisa Aulia; Permana, Enda; Rohendi, Dedi (Universitas Pendidikan Indonesia, 2020)
Student centered learning is the effective learning that can make learners develop. In order to conducteffective student center learning, media isimportancein the learning process.Mediacan create interesting, interactive learning, and students can learn independently. Research on media development is very important, whichcreate a media that able to support student centered learning. This study aims to produce multimedia animation and to determine students’responses ofthe application of multimedia onthe topic of material strength inthe concept of deflection.